Comparative study on the rumen ciliate populations in small experimental herds of water buffalo and Kedah Kelantan cattle in Malaysia - Imai, S.; Abdullah, N.; Ho, Y.W.; Jalaludin, S.; Hussain, H.Y.; Onodera, R.; Kudo, H. (Elsevier, 1995)
Seventeen ciliate species were identified from water buffalo and Kedah Kelantan cattle in Malaysia. Although most of these species have been detected from domestic ruminants in tropical and temperate areas, the presence of Metadinium ypsilon and Ostracodinium trivesiculatum is characteristic of Malaysian cattle and water buffalo. The average numbers of ciliates per milliliter of rumen contents were similar to those found in other areas. However, the level of Metadinium and Eudiplodinium, considered to be fermenters of cellulosic materials, was higher. This suggests that Malaysian cattle and water buffalo possess a ciliate protozoal composition favorable for digestion of cellulosic feed stuffs. There were no differences in the ciliate profile between the cattle and water buffalo. A similar pattern of diurnal change in the ciliate number of respective genera to that reported previously was also found in both Malaysian cattle and water buffalo.